13 reasons why. Season 2 [videorecording (DVD)] - Araki, Gregg; Moncrieff, Karen; Minnette, Dylan, 1996-; Langford, Katherine, 1996-; Navarro, Christian, 1991-; Asher, Jay, 1975- (Paramount, 2019)
After high school student Hannah Baker commits suicide, her friend Clay receives a box of tapes with messages she recorded beforehand explaining what drove her to the act.